Development of a Career Guidance Module for Elementary School Students: A Pedagogical Approach to Early Career Education - Rahim, Maryam; Hulukati, Wenny; Idris, Idriani; Yutapratama, Nicki; Alwi, Nurul Maulida (Educational Studies and Research Journal, 2025)
This study aims to develop a career development module for elementary school students. The research method employed Research and Development (R&D), which involved the following steps: (1) identifying potential and problems, (2) data collection, (3) product design, (4) design validation, (5) design revision, (6) product testing, and (7) product revision. Data were collected through questionnaires, including expert validation questionnaires and small group testing questionnaires. The data sources comprised three experts: a Career Guidance and Counseling expert, a Media Guidance and Counseling expert, an Indonesian language expert, and three elementary school teachers for the small group testing phase. Data analysis was conducted using qualitative methods to evaluate the results from expert validations and small-group testing. The research and development process produced an Elementary School Career Development Module deemed suitable for use in fostering career development among elementary school students. The module's feasibility was established through validations by career guidance and counseling experts, media design experts, Indonesian language experts, and small group testing conducted by guidance and counseling teachers and subject teachers at the elementary level. Therefore, the elementary school career development module is recommended to facilitate career development among elementary school students.